2021
DOI: 10.3389/fcimb.2021.780067
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Oral Microbiota Profiles in Chinese Patient With Oral Cancer

Abstract: Oral cancer is the most common malignant tumor in the oral and maxillofacial region, of which more than 90% is squamous cell carcinoma. The incidence of oral cancer is on the rise worldwide. An imbalance between the microorganism composition and its host may lead to the occurrence of oral malignant tumors. Accumulating evidence suggests that the oral microbiota plays an important role in oral cancer; however, the association between oral microbiota and oral cancer has not yet been comprehensively studied. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…It is also the first to compare the diversity between progressing and nonprogressing OED in a longitudinal design and to report on the functional potential of the bacteriome associated with risk of progression in OED. Our study has revealed that the bacterial make-up of the OED niche is similar to what has previously been described in the normal oral cavity, OPML and OSCC at the phylum and genus levels [29,60,[65][66][67]. We also found that although participant factors such as age or smoking status have an overall larger impact on the oral microbiome than progression status, once these are controlled for there are also small differences in the microbiome that can be attributed to progression status (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It is also the first to compare the diversity between progressing and nonprogressing OED in a longitudinal design and to report on the functional potential of the bacteriome associated with risk of progression in OED. Our study has revealed that the bacterial make-up of the OED niche is similar to what has previously been described in the normal oral cavity, OPML and OSCC at the phylum and genus levels [29,60,[65][66][67]. We also found that although participant factors such as age or smoking status have an overall larger impact on the oral microbiome than progression status, once these are controlled for there are also small differences in the microbiome that can be attributed to progression status (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Given that our study design compared samples taken at an early stage of disease (mild /moderate OED), the lack of significant differences between P and NPs may indicate that changes in overall diversity as well as taxonomic shifts occur at later stages in progression, or perhaps detectable only after OSCC has been established. Further to this, a study looking at OSCC, normal, and OPML found that while OSCC samples clustered based on betadiversity, pre-cancer and normal samples were mixed, indicating that there was not a great difference in the diversity between these groups [65]. This may support the notion that microbial changes in diversity change at a later stage.…”
Section: Discussionmentioning
confidence: 61%
“…For example, previous research indicated an important role of Fusobacterium and Capnocytophaga , two of the oral bacterial OTUs also found in this study, in the development of OSCC ( 21 , 22 ). In addition, this study showed that Prevotella intermedia was significantly enriched and distinct in all three OSCC sample types, which is consistent with the results of previous studies ( 23 ). P. intermedia , which carries and expresses interpain A, is a main cause of periodontitis ( 24 ).…”
Section: Discussionsupporting
confidence: 92%
“…As mentioned earlier, the fluctuations in the quantity of bacterial species in the oral flora can, in some instances, lead to periodontal [ 25 ] and malignant lesions [ 26 ]. This effect can be amplified when accompanied by other factors including NLRP3 in developing periodontitis [ 27 ] and genetic polymorphisms, such as MTHFR mutations, which is an important factor to consider for oral cancer [ 28 ].…”
Section: Discussionmentioning
confidence: 99%